Sodium absorption stimulator prostasin (PRSS8) has an anti-inflammatory effect via downregulation of TLR4 signaling in inflammatory bowel disease - Sugitani, Yoshihiko; Nishida, Atsushi; Inatomi, Osamu; Ohno, Masashi; Imai, Takayuki; Kawahara, Masahiro; Kitamura, Kenichiro; Andoh, Akira (Journal of gastroenterology, 2020)
Background Prostasin (PRSS8) is a stimulator of epithelial sodium transport. In this study, we evaluated alteration of prostasin expression in the inflamed mucosa of patients with inflammatory bowel disease (IBD) and investigated the role of prostasin in the gut inflammation. Methods Prostasin expression was evaluated by immunohistochemical staining. Dextran sodium sulfate (DSS)-colitis was induced in mice lacking prostasin specifically in intestinal epithelial cells ( PRSS8 ΔIEC mice). Results In colonic mucosa of healthy individuals, prostasin was strongly expressed at the apical surfaces of epithelial cells, and this was markedly decreased in active mucosa of both ulcerative colitis and Crohn’s disease. DSS-colitis was exacerbated in PRSS8 ΔIEC mice compared to control PRSS8 lox/lox mice. Toll-like receptor4 (TLR4) expression in colonic epithelial cells was stronger in DSS-treated PRSS8 ΔIEC mice than in DSS-treated PRSS8 lox/lox mice. NF-κB activation in colonic epithelial cells was more pronounced in DSS-treated PRSS8 ΔIEC mice than in DSS-treated PRSS8 lox/lox mice, and the mRNA expression of inflammatory cytokines was significantly higher in DSS-treated PRSS8 ΔIEC mice. Broad-spectrum antibiotic treatment completely suppressed the exacerbation of DSS-colitis in PRSS8 ΔIEC mice. The mRNA expression of tight junction proteins and mucosal permeability assessed using FITC-dextran were comparable between DSS-treated PRSS8 lox/lox and DSS-treated PRSS8 ΔIEC mice. Conclusion Prostasin has an anti-inflammatory effect via downregulation of TLR4 expression in colonic epithelial cells. Reduced prostasin expression in IBD mucosa is linked to the deterioration of local anti-inflammatory activity and may contribute to the persistence of mucosal inflammation.